2020
DOI: 10.1155/2020/8852307
|View full text |Cite
|
Sign up to set email alerts
|

Human Periodontal Ligament Stem Cell-Derived Exosomes Promote Bone Regeneration by Altering MicroRNA Profiles

Abstract: The role and underlying mechanism of exosomes derived from human periodontal ligament stem cells (PDLSC) in osteogenesis are unclear. In the present study, we identified the exosomes derived from PDLSCs and found that osteogenic induction can enhance the osteogenic ability of PDLSC-derived exosomes in promoting the osteogenic differentiation of rat bone marrow stem cells (BMSCs). To investigate the underlying mechanism, we analyzed the exosomal miRNA expression profiles of undifferentiated and osteogenic diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 57 publications
2
38
0
Order By: Relevance
“…The exosomes isolated from PDLSCs that were exposed to the LPS-induced periodontitis environment demonstrated good anti-inflammatory ability by modulating the balance of T helper cell 17 (Th17)/regulatory T cell (Treg) through the miR-155-5p/SIRT1 pathway ( Zheng et al, 2019 ). In terms of osteogenesis, PDLSC-Exos possess the capacity for inducing osteogenic differentiation of BMMSCs via regulating AMPK signaling, MAPK signaling, and insulin signaling pathways ( Liu et al, 2020 ). P2X7R overexpressing PDLSCs-derived conditional medium and exosomes markedly improved the osteogenic capacity of PDLSCs in the inflammatory microenvironment by delivering miR-3679-5p, miR-6515-5p, and miR-6747-5p ( Xu X. Y. et al, 2020 ).…”
Section: Translational and Clinical Applications Of Dental Stem Cell-derived Exosomesmentioning
confidence: 99%
“…The exosomes isolated from PDLSCs that were exposed to the LPS-induced periodontitis environment demonstrated good anti-inflammatory ability by modulating the balance of T helper cell 17 (Th17)/regulatory T cell (Treg) through the miR-155-5p/SIRT1 pathway ( Zheng et al, 2019 ). In terms of osteogenesis, PDLSC-Exos possess the capacity for inducing osteogenic differentiation of BMMSCs via regulating AMPK signaling, MAPK signaling, and insulin signaling pathways ( Liu et al, 2020 ). P2X7R overexpressing PDLSCs-derived conditional medium and exosomes markedly improved the osteogenic capacity of PDLSCs in the inflammatory microenvironment by delivering miR-3679-5p, miR-6515-5p, and miR-6747-5p ( Xu X. Y. et al, 2020 ).…”
Section: Translational and Clinical Applications Of Dental Stem Cell-derived Exosomesmentioning
confidence: 99%
“…Compared with undifferentiated PDLSCs EVs, 3 circRNAs and 2 lncRNAs were upregulated and 39 circRNAs and 5 lncRNAs were downregulated consistently after 5 and 7 days of exposure to differentiation medium [ 52 ]. Moreover, 72 miRNAs were upregulated while 35 were downregulated in PDLSCs EXOs after osteogenic induction [ 53 ].…”
Section: Mscs Secretomementioning
confidence: 99%
“…However, scientists have now found that there are dual origins of DPSCs. Suppress: CD3 + T cells [83]; Th17 cells [84]; B cells [83]; dendritic cells [69]; M1 macrophages [203] PDLSC-CM: enhance periodontal regeneration [81] Exosomes: enhance the osteogenic ability of BMMSCs [82] Hypoxia: increase osteogenic [88] TNF-α, IL-1β: increase angiogenesis & tissue regeneration [89] DPSCs Suppress: PBMCs [114,119] (T cells [115][116][117]204], B cells [118])…”
Section: In Vitro Characterization Of Dental Pulp Stem Cellsmentioning
confidence: 99%
“…PDLSC-conditioned medium (CM), which contains the paracrine factors, can enhance periodontal regeneration in rats with surgically created periodontal defects by suppressing the inflammatory response through TNF- α production [ 81 ]. Exosomes from osteogenic-inducted PDLSCs can enhance the osteogenic ability of BMMSCs [ 82 ].…”
Section: Periodontal Ligament Stem Cellsmentioning
confidence: 99%